PENGARUH DESENTRALISASI, STRATEGI BISNIS DAN PEMANFAATAN INFORMASI SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL PADA PT BANK MANDIRI DI MANADO - Senduk, Jilie Maria; Ilat, Ventje; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
To be able to leading in today's global competition, companies must have an effective, fast and precise decision-making level. PT Bank Mandiri is the largest BUMN banking services company in Indonesia that has expanded overseas. This research aimed to examine the influence of decentralization, business strategy and the utilization of information management accounting system on managerial performance at PT Bank Mandiri in Manado. Population in this research are the managers and officers on manager level at Bank Mandiri Area Manado and Mandiri KCP Manado. This research used purposive sampling technique. This research used questionnaires to collect data from 34 respondents. This research used primary data obtained questionnaires. Data analysis was performed with multiple linear regression analysis. The result of this research showed that decentralization has a significant positive effect on managerial performance, business strategy has not effect on managerial performance and information management accounting system has a significant positive effect on managerial performance at PT Bank Mandiri in Manado.Keywords: Decentralization, Business Strategy, Information Management Accounting System, Managerial Performance